Iron-zinc-zirconium composite oxide-molecular sieve catalyst, and preparation method and application thereof
Patent Information
- Application Number
- CN202611351102.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-16
AI Technical Summary
另一相关技术公开了一种InZrOx/H-SSZ-13复合催化剂,在CO2加氢过程中,LPG在总烃中选择性达到90%,CO2转化率为25%,但CO副产物选择性超过60%,导致LPG收率仅为9%
[0017] The preparation method of the iron-zinc-zirconium composite oxide-molecular sieve catalyst provided by this invention is simple to operate, low in cost, and free from secondary pollution, making it suitable for industrial production.
Smart Images

Figure CN122912908A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst technology, specifically relating to an iron-zinc-zirconium composite oxide-molecular sieve catalyst, its preparation method, and its application. Background Technology
[0002] Through catalytic hydrogenation with renewable green hydrogen, CO2 can be selectively converted to produce high-value-added oils and chemicals. This not only effectively reduces the serious environmental problems caused by large-scale CO2 emissions but also opens up new non-petroleum routes for the production of important chemicals. Therefore, the production of high-value-added chemicals and fuels through CO2 hydrogenation has enormous potential in the development of clean energy and plays a crucial role in realizing the resource utilization of CO2 and reducing carbon emissions.
[0003] CO2 hydrogenation can produce a variety of high-value-added products, including olefins, aromatics, liquefied petroleum gas (LPG), and gasoline and diesel. LPG is an important basic chemical feedstock. Its main components are propane and butane, which burn relatively completely without producing particulate matter, making it an environmentally friendly clean fuel widely used in residential, commercial, and agricultural heating applications. Simultaneously, LPG can also be used as an aerosol propellant and refrigerant to replace chlorofluorocarbons (CFCs) and reduce damage to the Earth's ozone layer. Furthermore, LPG can also be used as a chemical feedstock to produce propylene and butene through dehydrogenation.
[0004] Significant progress has been made in the hydrogenation of CO2 to LPG. One related technology discloses an FeCo bimetallic catalyst that can achieve CO2 hydrogenation to LPG; under conditions of 320℃ and 3.0 MPa, the CO2 conversion exceeds 40%, but the LPG selectivity is only 43.6%, and the LPG yield is 17.4%. Another related technology discloses an InZrO... x The / H-SSZ-13 composite catalyst achieves a 90% selectivity for LPG in total hydrocarbons and a 25% CO2 conversion rate during CO2 hydrogenation. However, the selectivity for CO byproducts exceeds 60%, resulting in an LPG yield of only 9%. In summary, the existing technology suffers from low CO2 conversion, low LPG selectivity, and low yield. Summary of the Invention
[0005] The purpose of this invention is to provide an iron-zinc-zirconia composite oxide-molecular sieve catalyst, its preparation method, and its applications. The iron-zinc-zirconia composite oxide-molecular sieve catalyst provided by this invention exhibits high CO2 conversion rate, high selectivity for liquefied petroleum gas, and high yield.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A zinc-zirconium composite oxide-molecular sieve catalyst includes a zinc-zirconium composite oxide and an acidic H-RHO molecular sieve; the zinc-zirconium composite oxide contains 0.1-4% iron by mass and the molar ratio of zinc to zirconium is 0.1-1:1.
[0007] Preferably, the mass ratio of the iron-zinc-zirconium composite oxide to the acidic H-RHO molecular sieve is 0.2~4:1.
[0008] Preferably, the silicon-to-aluminum atomic ratio of the acidic H-RHO molecular sieve is 0.01~0.4:1; the size of the acidic H-RHO molecular sieve is 1~3μm; and the particle size of the iron-zinc-zirconium composite oxide is 5~10nm.
[0009] This invention provides a method for preparing the iron-zinc-zirconium composite oxide-molecular sieve catalyst described above, comprising the following steps: A composite metal ion salt solution is obtained by mixing water-soluble iron salt, water-soluble zinc salt, water-soluble zirconium salt, and water. The composite metal ion salt solution and the organic complexing agent were mixed to carry out a complexation reaction to obtain a colloidal solid precursor. The colloidal solid precursor was calcined to obtain an iron-zinc-zirconium composite oxide. The iron-zinc-zirconium composite oxide is mixed with acidic H-RHO molecular sieve to obtain the iron-zinc-zirconium composite oxide-molecular sieve catalyst.
[0010] Preferably, the molar ratio of total metal ions to organic complexing agent in the composite metal ion salt solution is 1:0.25~5.
[0011] Preferably, the organic complexing agent includes one or more of glucose, citric acid, salicylic acid, and tartaric acid; the complexation reaction is carried out at a temperature of 50-90°C for 2-10 hours.
[0012] Preferably, the calcination temperature is 300~800℃ and the holding time is 2~10h; the iron-zinc-zirconium composite oxide and the acidic H-RHO molecular sieve are mixed by mechanical grinding.
[0013] This invention provides the application of the iron-zinc-zirconium composite oxide-molecular sieve catalyst described in the above technical solution or the iron-zinc-zirconium composite oxide-molecular sieve catalyst prepared by the above preparation method in the production of liquefied petroleum gas by carbon dioxide hydrogenation.
[0014] This invention provides a method for producing liquefied petroleum gas (LPG) by catalytic hydrogenation of carbon dioxide using an iron-zinc-zirconium composite oxide-molecular sieve catalyst, comprising the following steps: The iron-zinc-zirconium composite oxide-molecular sieve catalyst was subjected to reduction pretreatment to obtain a reduction catalyst; The mixture of H2 and CO2 is subjected to a hydrogenation reaction under the catalysis of the reduction catalyst to obtain liquefied petroleum gas; The iron-zinc-zirconia composite oxide-molecular sieve catalyst is the iron-zinc-zirconia composite oxide-molecular sieve catalyst described in the above technical solution or the iron-zinc-zirconia composite oxide-molecular sieve catalyst prepared by the above preparation method.
[0015] Preferably, the reduction pretreatment is carried out in a hydrogen atmosphere, and the temperature of the reduction pretreatment is 300~500℃, and the time is 1~6h; The volume ratio of H2 to CO2 is 1~8:1; The space velocity of the H2 and CO2 mixture is 800~10000 mL / (h·g); The hydrogenation reaction is carried out at a temperature of 300~420℃, for a time of 10~1000h, and at a pressure of 0.5~6MPa.
[0016] The iron-zinc-zirconia composite oxide-molecular sieve catalyst provided by this invention comprises an iron-zinc-zirconia composite oxide and an acidic H-RHO molecular sieve. In the iron-zinc-zirconia composite oxide, strong interactions exist at the interface between the iron oxide and zinc-zirconia oxide, thereby promoting CO2 adsorption and H2 dissociation, which is beneficial to the formation of methanol intermediates. Simultaneously, it inhibits the counter-current water-gas reaction, which competes with methanol formation, reducing the formation of CO byproducts. The acidic H-RHO molecular sieve possesses a supercage structure with double eight-membered ring pores and strong acidity, enabling the directional conversion of methanol intermediates into liquefied petroleum gas.
[0017] The preparation method of the iron-zinc-zirconium composite oxide-molecular sieve catalyst provided by this invention is simple to operate, low in cost, and free from secondary pollution, making it suitable for industrial production.
[0018] This invention uses an iron-zinc-zirconium composite oxide-molecular sieve catalyst for the catalytic hydrogenation of carbon dioxide to produce liquefied petroleum gas (LPG). According to the application example, the CO2 conversion rate is 62.41%, the LPG selectivity in total hydrocarbons is 78.28%, the LPG yield is 32.94%, and the catalyst stability is over 500 hours. Attached Figure Description
[0019] Figure 1 The X-ray diffraction (XRD) pattern of the iron-zinc-zirconium composite oxide prepared in Example 1; Figure 2 Transmission electron microscope (TEM) image of the iron-zinc-zirconium composite oxide prepared in Example 1; Figure 3 The figure shows the catalytic performance of the iron-zinc-zirconium composite oxide-molecular sieve catalyst prepared in Example 1 in the reaction of carbon dioxide hydrogenation to liquefied petroleum gas. Detailed Implementation
[0020] In this invention, unless otherwise specified, all raw materials / components used in the preparation are commercially available products well known to those skilled in the art.
[0021] This invention provides an iron-zinc-zirconia composite oxide-molecular sieve catalyst, comprising an iron-zinc-zirconia composite oxide and an acidic H-RHO molecular sieve; wherein the iron content in the iron-zinc-zirconia composite oxide is 0.1-4% by mass, and the molar ratio of zinc to zirconium is 0.1-1:1.
[0022] The iron-zinc-zirconia composite oxide-molecular sieve catalyst provided by this invention comprises an iron-zinc-zirconia composite oxide, wherein the mass percentage of iron in the iron-zinc-zirconia composite oxide is 0.1-4%, and the molar ratio of zinc to zirconium is 0.1-1:1. In one embodiment of this invention, the iron-zinc-zirconia composite oxide is formed by combining iron oxide, zinc oxide, and zirconium oxide, wherein the iron oxide is FeO and Fe2O3; the mass percentage of iron in the iron-zinc-zirconia composite oxide can further be 0.3-3%, more further 0.5-3%, specifically 0.5%, 1.5%, or 3%; the molar ratio of zinc to zirconium is 0.1-1:1, further 0.2-0.8:1, and more further 0.3-0.6:1; the molar amount of oxygen in the iron-zinc-zirconia composite oxide satisfies the condition that the total valence of the iron-zinc-zirconia composite oxide is zero. The particle size of the iron-zinc-zirconia composite oxide is 5-10 nm.
[0023] The iron-zinc-zirconium composite oxide-molecular sieve catalyst provided by this invention includes an acidic H-RHO molecular sieve. In one embodiment of this invention, the silicon-to-aluminum atomic ratio of the acidic H-RHO molecular sieve is 0.01~0.4:1, more further 0.02~0.3:1, and even more further 0.04~0.25:1, specifically 0.1:1, 0.2:1, or 0.25:1; the morphology of the acidic H-RHO molecular sieve is a cubic polyhedral structure with a grain size of 1~3 μm. The acidic H-RHO molecular sieve has an eight-membered ring supercage structure and exhibits strong acid properties, enabling it to promote the conversion of methanol intermediates to LPG. The preparation method of the acidic H-RHO molecular sieve is discussed in detail later.
[0024] In one embodiment of the present invention, the mass ratio of the iron-zinc-zirconium composite oxide to the acidic H-RHO molecular sieve is 0.2~4:1, further 0.5~3:1, and even further 1~2:1.
[0025] In one embodiment of the present invention, the particle size of the iron-zinc-zirconia composite oxide-molecular sieve catalyst is 10-80 mesh, more specifically 20-60 mesh, and even more specifically 20-40 mesh. In the iron-zinc-zirconia composite oxide-molecular sieve catalyst, both the iron-zinc-zirconia composite oxide and the acidic H-RHO molecular sieve are active components. The iron-zinc-zirconia composite oxide is responsible for CO2 adsorption and activation to generate methanol intermediates, while the molecular sieve is responsible for converting methanol intermediates into LPG.
[0026] The preparation method of the acidic H-RHO molecular sieve is described in detail below, including the following steps: A gel system is obtained by mixing silicon source, aluminum source, phosphorus source, template agent, crystallization aid and water; The gel system was crystallized to obtain RHO molecular sieves; The RHO molecular sieve was calcined to obtain acidic H-RHO molecular sieve.
[0027] This invention mixes a silicon source, an aluminum source, a phosphorus source, a template agent, a crystallization aid, and water to obtain a gel system. In one embodiment of the present invention, the silicon source includes tetraethyl orthosilicate (TEOS), the aluminum source includes aluminum isopropoxide (AIP), the phosphorus source includes phosphoric acid (H3PO4), the template agent includes diethylamine (DEA), the crystallization aid includes hexadecyltrimethylammonium bromide (CTAB), and the water is preferably deionized water; in the gel system, the molar ratio of SiO2:Al2O3:H3PO4:DEA:CTAB:H2O is (0.02~0.8):1.0:0.8:2.0:0.15:50, and can further be (0.05~0.6):1.0:0.8:2.0:0.15:50, specifically 0.2:1.0:0.8:2.0:0.15:50 or 0.4:1.0:0.8:2.0:0.15:50 or 0.5:1.0:0.8:2.0:0.15:50.
[0028] After obtaining the gel system, the present invention performs crystallization treatment on the gel system to obtain RHO molecular sieves. In one embodiment of the present invention, the crystallization treatment temperature can be 150~200℃, the time can be 10~40h, more specifically 10~20h, and more specifically 12h; the crystallization treatment further includes: sequentially centrifuging, washing, and drying the obtained molecular sieve. The present invention does not specifically limit the parameters for centrifugation, washing, and drying; centrifugation, washing, and drying methods well known to those skilled in the art can be used.
[0029] After obtaining the RHO molecular sieve, the present invention calcines the RHO molecular sieve to obtain acidic H-RHO molecular sieve. In one embodiment of the present invention, the calcination temperature can be 500~600℃, and the time can be 5~15h, specifically 10h.
[0030] This invention provides a method for preparing the iron-zinc-zirconium composite oxide-molecular sieve catalyst described above, comprising the following steps: A composite metal ion salt solution is obtained by mixing water-soluble iron salt, water-soluble zinc salt, water-soluble zirconium salt, and water. The composite metal ion salt solution and an organic complexing agent are mixed to carry out a complexation reaction, thereby obtaining a colloidal solid precursor. The colloidal solid precursor was calcined to obtain an iron-zinc-zirconium composite oxide. The iron-zinc-zirconium composite oxide is mixed with acidic H-RHO molecular sieve to obtain the iron-zinc-zirconium composite oxide-molecular sieve catalyst.
[0031] This invention mixes water-soluble iron salt, water-soluble zinc salt, water-soluble zirconium salt, and water to obtain a composite metal ion salt solution. In one embodiment of this invention, the water-soluble iron salt includes ferric nitrate, ferric chloride, or ferric sulfate, preferably ferric nitrate; the water-soluble zinc salt includes zinc nitrate, zinc chloride, or zinc sulfate, preferably zinc nitrate; the water-soluble zirconium salt includes water-soluble zirconium nitrate, zirconium chloride, or zirconium sulfate, preferably zirconium nitrate; and the water is preferably deionized water.
[0032] In one embodiment of the present invention, the concentration of iron ions in the composite metal ion salt solution can be 0.001~0.02 mol / L, more preferably 0.002~0.011 mol / L, and even more preferably 0.005~0.01 mol / L; the concentration of zinc ions can be 0.02~0.1 mol / L, more preferably 0.02~0.08 mol / L, and even more preferably 0.03~0.05 mol / L, specifically 0.04 mol / L; the concentration of zirconium ions can be 0.05~0.2 mol / L, more preferably 0.08~0.15 mol / L, and even more preferably 0.1~0.13 mol / L.
[0033] After obtaining the composite metal ion salt solution, the present invention mixes the composite metal ion salt solution with an organic complexing agent to carry out a complexation reaction, thereby obtaining a colloidal solid precursor. As one embodiment of the present invention, the organic complexing agent includes one or more of glucose, citric acid, salicylic acid, and tartaric acid, preferably glucose; when the organic complexing agent has two or more components, the present invention does not have a special limitation on the mass ratio of each component of the organic complexing agent, and they can be added in any proportion.
[0034] In one embodiment of the present invention, the molar ratio of total metal ions to organic complexing agent in the composite metal ion salt solution is 1:0.25~5, further can be 1:1~4, and even further can be 1:2~3. By controlling the molar ratio of total metal ions to organic complexing agent in the composite metal ion salt solution within the above range, the present invention can effectively promote the complexation of metal ions with the organic complexing agent to form a colloidal solid precursor.
[0035] In one embodiment of the present invention, the temperature of the complexation reaction can be 50~90℃, further can be 60~85℃, and even further can be 65~80℃; the time is 2~10h, further can be 4~8h, and even further can be 5~7h.
[0036] After obtaining the colloidal solid precursor, the present invention calcines the colloidal solid precursor to obtain an iron-zinc-zirconium composite oxide. As one embodiment of the present invention, the calcination process further includes drying the colloidal solid precursor; the drying temperature can be 60~140℃, more specifically 70~120℃, and more specifically 100℃, for 3~15 hours, and more specifically 5~12 hours; the drying is carried out in an oven.
[0037] In one embodiment of the present invention, the calcination temperature can be 300~800℃, more specifically 350~700℃, and more specifically 500℃; the holding time is 2~10h, and more specifically 3~8h; the calcination atmosphere is an air atmosphere; and the calcination is carried out in a muffle furnace.
[0038] The iron-zinc-zirconium composite oxide prepared by the sol-gel method of the present invention exhibits strong interaction between the iron oxide and zinc-zirconium oxide interfaces, thereby promoting the adsorption and activation of CO2 and H2, which is beneficial to the formation of methanol intermediate.
[0039] After obtaining the iron-zinc-zirconium composite oxide, the present invention mixes the iron-zinc-zirconium composite oxide with acidic H-RHO molecular sieve to obtain the iron-zinc-zirconium composite oxide-molecular sieve catalyst. As one embodiment of the present invention, the mixing of the iron-zinc-zirconium composite oxide with the acidic H-RHO molecular sieve can be mechanical grinding. The present invention does not have specific limitations on the parameters of the mechanical grinding mixture; any mechanical grinding scheme well known to those skilled in the art can be used.
[0040] In one embodiment of the present invention, the mechanical grinding and mixing process further includes: sequentially pressing, crushing, and sieving the ground mixture to obtain an iron-zinc-zirconium composite oxide-molecular sieve catalyst. The present invention does not impose any special limitations on the pressing, crushing, and sieving operations; any pressing, crushing, and sieving techniques well-known to those skilled in the art can be used. The present invention improves the strength of the catalyst through pressing, preventing the powder from being blown away during the gas-solid reaction.
[0041] This invention provides the application of the iron-zinc-zirconium composite oxide-molecular sieve catalyst described in the above technical solution or the iron-zinc-zirconium composite oxide-molecular sieve catalyst prepared by the above preparation method in the production of liquefied petroleum gas by carbon dioxide hydrogenation.
[0042] This invention provides a method for producing liquefied petroleum gas (LPG) by catalytic hydrogenation of carbon dioxide using an iron-zinc-zirconium composite oxide-molecular sieve catalyst, comprising the following steps: The iron-zinc-zirconium composite oxide-molecular sieve catalyst was subjected to reduction pretreatment to obtain a reduction catalyst; The mixture of H2 and CO2 is subjected to a hydrogenation reaction under the catalysis of the reduction catalyst to obtain liquefied petroleum gas; The iron-zinc-zirconia composite oxide-molecular sieve catalyst is the iron-zinc-zirconia composite oxide-molecular sieve catalyst described in the above technical solution or the iron-zinc-zirconia composite oxide-molecular sieve catalyst prepared by the above preparation method.
[0043] This invention involves reducing a zinc-zirconia composite oxide-molecular sieve catalyst to obtain a reduced catalyst. In one embodiment, the reduction pretreatment is performed under a hydrogen atmosphere. The temperature of the reduction pretreatment can be 300-500°C, more specifically 350-450°C, and even more specifically 350-400°C; the time can be 1-6 hours, more specifically 2-5 hours, and even more specifically 2-4 hours.
[0044] This invention involves hydrogenating a mixture of H2 and CO2 under the catalytic action of a reduction catalyst to obtain liquefied petroleum gas. In one embodiment of the present invention, the volume ratio of H2 to CO2 is 1~8:1, further can be 2~6:1, and even further can be 3~6:1; the space velocity of the H2 and CO2 mixture is 800~10000 mL / (h·g), further can be 900~8000 mL / (h·g), and even further can be 1000~6000 mL / (h·g), specifically 1000~4000 mL / (h·g); the temperature of the hydrogenation reaction is 300~420℃, further can be 320~400℃, and even further can be 350~375℃; the time is 10~1000h, further can be 30~700h, and even further can be 30~500h; the pressure is 0.5~6MPa, further can be 1~5MPa, and even further can be 2~4MPa, specifically 3~4MPa.
[0045] To further illustrate the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments thereof. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0046] Preparation Example 1 Tetraethyl orthosilicate (TEOS), aluminum isopropoxide (AIP), phosphoric acid (H3PO4), diethylamine (DEA), hexadecyltrimethylammonium bromide (CTAB), and water were mixed to form a gel system. The molar ratio of SiO2:Al2O3:H3PO4:DEA:CTAB:H2O in the gel system was 0.2:1.0:0.8:2.0:0.15:50. The gel system was poured into a stainless steel reactor with a polytetrafluoroethylene liner and crystallized at 200°C for 12 hours. The resulting material was then separated, washed, and dried to obtain RHO molecular sieve raw powder. The RHO molecular sieve raw powder was calcined at 600°C for 10 hours to obtain acidic H-RHO molecular sieve with a silicon-to-aluminum atomic ratio of 0.1.
[0047] Preparation Example 2 The preparation method is basically the same as in Example 1, except that the molar ratio of SiO2:Al2O3:H3PO4:DEA:CTAB:H2O in the gel system is 0.4:1.0:0.8:2.0:0.15:50; thus, acidic H-RHO molecular sieves with a silicon-to-aluminum atomic ratio of 0.2 are obtained.
[0048] Preparation Example 3 The preparation method is basically the same as in Example 1, except that the molar ratio of SiO2:Al2O3:H3PO4:DEA:CTAB:H2O in the gel system is 0.5:1.0:0.8:2.0:0.15:50; thus, acidic H-RHO molecular sieves with a silicon-to-aluminum atomic ratio of 0.25 are obtained.
[0049] Example 1 (1) Ferric nitrate (3.27 g, 0.008 mol), zinc nitrate (17.85 g, 0.06 mol), and zirconium nitrate (85.86 g, 0.2 mol) were dissolved in 1500 mL of deionized water and stirred to obtain an iron-zinc-zirconium composite metal ion salt solution; the iron-zinc-zirconium composite metal ion salt solution was mixed with glucose (159.33 g, 0.80 mol) and subjected to a complexation reaction at 80 °C for 5 h to obtain a colloidal solid precursor; the colloidal solid precursor was transferred to a 100 °C oven and dried for 12 h to obtain an iron-zinc-zirconium composite oxide solid precursor; the iron-zinc-zirconium composite oxide solid precursor was transferred to a muffle furnace and calcined at 500 °C in air atmosphere for 3 h to obtain an iron-zinc-zirconium composite oxide (1.5% Fe / Zn). 0.6 Zr 2.0 O 4.72 1.5%Fe indicates that the mass percentage of iron in the iron-zinc-zirconium composite oxide is 1.5%.
[0050] (2) The iron-zinc-zirconium composite oxide was ground and mixed with the acidic H-RHO molecular sieve (silicon-aluminum atomic ratio of 0.1) prepared in Preparation Example 1 at a mass ratio of 1:2. The ground mixture was then pressed, crushed and sieved in sequence to obtain an iron-zinc-zirconium composite oxide-molecular sieve catalyst with a particle size of 20-40 mesh.
[0051] Figure 1 The XRD pattern of the iron-zinc-zirconium composite oxide prepared in Example 1; according to Figure 1 It can be seen that the prepared iron-zinc-zirconium composite oxide exhibits a solid solution structure.
[0052] Figure 2 TEM image of the iron-zinc-zirconium composite oxide prepared in Example 1; according to Figure 2 It can be seen that the prepared iron-zinc-zirconium composite oxide exhibits a spherical particle packing morphology.
[0053] Example 2 Step (1) is basically the same as in Example 1, except that the amount of ferric nitrate added is (1.21 g, 0.003 mol); the amount of glucose added is (156.36 g, 0.79 mol); and an iron-zinc-zirconium composite oxide (0.5% FeO) is obtained. y -Zn 0.6 Zr2.0 O 4.645 0.5%Fe indicates that the mass percentage of iron in the iron-zinc-zirconium composite oxide is 0.5%.
[0054] Step (2) is the same as in Example 1, and an iron-zinc-zirconium composite oxide-molecular sieve catalyst with a particle size of 20-40 mesh is obtained.
[0055] Example 3 Step (1) is basically the same as in Example 1, except that the amount of ferric nitrate added is (6.69 g, 0.0165 mol); the amount of glucose added is (164.42 g, 0.83 mol); and an iron-zinc-zirconium composite oxide (3% FeO) is obtained. y -Zn 0.6 Zr 2.0 O 4.85 3%Fe indicates that the mass percentage of iron in the iron-zinc-zirconium composite oxide is 3%.
[0056] Step (2) is the same as in Example 1, and an iron-zinc-zirconium composite oxide-molecular sieve catalyst with a particle size of 20-40 mesh is obtained.
[0057] Example 4 Step (1) is the same as in Example 1.
[0058] Step (2) is basically the same as in Example 1, except that the acidic H-RHO molecular sieve prepared in Example 1 is replaced with the acidic H-RHO molecular sieve prepared in Example 2 (silicon-aluminum atomic ratio is 0.2) to obtain an iron-zinc-zirconium composite oxide-molecular sieve catalyst with a particle size of 20-40 mesh.
[0059] Example 5 Step (1) is the same as in Example 1.
[0060] Step (2) is basically the same as in Example 1, except that the acidic H-RHO molecular sieve prepared in Preparation Example 1 is replaced with the acidic H-RHO molecular sieve prepared in Preparation Example 3 (silicon-aluminum atomic ratio is 0.25) to obtain an iron-zinc-zirconium composite oxide-molecular sieve catalyst with a particle size of 20-40 mesh.
[0061] Comparative Example 1 Step (1) is basically the same as in Example 1, except that the addition of ferric nitrate is omitted, and the amount of glucose added is (154.57g, 0.78mol); zinc-zirconium composite oxide (Zn) is obtained. 0.6 Zr 2.0 O 4.6 ).
[0062] Step (2) is the same as in Example 1, and a zinc-zirconium composite oxide-molecular sieve catalyst with a particle size of 20-40 mesh is obtained.
[0063] Comparative Example 2 Step (1) is basically the same as in Example 1, except that the addition of ferric nitrate is omitted, and the amount of glucose added is (154.57g, 0.78mol); zinc-zirconium composite oxide (Zn) is obtained. 0.6 Zr 2.0 O 4.6 ).
[0064] Step (2) involves placing the zinc-zirconium composite oxide (Zn) 0.6 Zr 2.0 O 4.6 When 1,000 ions are mixed with Fe2O3, 1.5% Fe + Zn is obtained. 0.6 Zr 2.0 O 4.6 Composite oxide (1.5%Fe indicates that the mass percentage of iron in the composite oxide is 3%).
[0065] Step (3) is the same as step (2) in Example 1, yielding 1.5% Fe+Zn with a particle size of 20-40 mesh. 0.6 Zr 2.0 O 4.6 Iron-zinc-zirconium composite oxide-molecular sieve catalyst.
[0066] Comparative Example 3 Step (1) is the same as in Example 1.
[0067] Step (2) is basically the same as in Example 1, except that the acidic H-RHO molecular sieve prepared in Example 1 is replaced with acidic H-SAPO-34 molecular sieve (silicon-aluminum atomic ratio is 0.2) to obtain an iron-zinc-zirconium composite oxide-acidic H-SAPO-34 molecular sieve catalyst with a particle size of 20~40 mesh.
[0068] The preparation method of acidic H-SAPO-34 molecular sieve (silicon-to-aluminum atomic ratio of 0.2) is as follows: Silica sol (JN-40), boehmite (NaAlO2), tetraethylammonium hydroxide (TEAOH), sodium hydroxide (NaOH), phosphoric acid (H3PO4), and water are mixed to form a gel system. The molar ratio of SiO2:Al2O3:TEAOH:NaOH:H3PO4:H2O in the gel system is 1:2.5:40:0.15:40:1400. The gel system is poured into a stainless steel reactor with a polytetrafluoroethylene liner and crystallized at 200℃ for 22 hours. The resulting material is then separated, washed, and dried to obtain SAPO-34 molecular sieve powder. The SAPO-34 molecular sieve powder is calcined at 560℃ for 10 hours to obtain acidic H-SAPO-34 molecular sieve with a silicon-to-aluminum atomic ratio of 0.2.
[0069] Comparative Example 4 Step (1) is the same as in Example 1.
[0070] Step (2) is basically the same as in Example 1, except that the acidic H-RHO molecular sieve prepared in Example 1 is replaced with acidic H-ZSM-5 molecular sieve (silicon-aluminum atomic ratio of 40) to obtain an iron-zinc-zirconium composite oxide-acidic H-ZSM-5 molecular sieve catalyst with a particle size of 20~40 mesh.
[0071] The preparation method of acidic H-ZSM-5 molecular sieve (silicon-to-aluminum atomic ratio of 40) is as follows: Silica sol, sodium aluminate, tetrapropylammonium hydroxide (TPAOH), sodium hydroxide, and water are mixed to form a gel system. The molar ratio of SiO2:Al2O3:TPAOH:NaOH:H2O in the gel system is 1:0.0125:0.15:0.18:12. The gel system is poured into a stainless steel reactor with a polytetrafluoroethylene liner and incubated at 170°C. After crystallization for 48 hours, the resulting material was sequentially separated, washed, and dried to obtain NaZSM-5 molecular sieve raw powder. The NaZSM-5 molecular sieve raw powder was calcined at 560℃ for 10 hours, and then subjected to ammonium exchange with ammonium nitrate aqueous solution for 5 hours. The resulting material was sequentially separated, washed, and dried to obtain H-ZSM-5 molecular sieve raw powder. The H-ZSM-5 molecular sieve raw powder was calcined at 560℃ for 6 hours to obtain acidic H-ZSM-5 molecular sieve with a silicon-to-aluminum atomic ratio of 40.
[0072] Comparative Example 5 Step (1) is the same as in Example 1.
[0073] Step (2) is basically the same as in Example 1, except that the acidic H-RHO molecular sieve prepared in Example 1 is replaced with acidic H-ZSM-11 molecular sieve (silicon-aluminum atomic ratio of 50) to obtain an iron-zinc-zirconium composite oxide-acidic H-ZSM-11 molecular sieve catalyst with a particle size of 20-40 mesh.
[0074] The preparation method of acidic H-ZSM-11 molecular sieve (silicon-to-aluminum atomic ratio of 50) is as follows: Silica sol, sodium aluminate, tetrabutylammonium hydroxide (TBAOH), sodium hydroxide, and water are mixed to form a gel system. The molar ratio of SiO2:Al2O3:TBAOH:NaOH:H2O in the gel system is 1:0.01:0.1:0.15:12. The gel system is poured into a stainless steel reactor with a polytetrafluoroethylene liner and crystallized at 170℃. After 20 hours, the obtained material was sequentially separated, washed, and dried to obtain NaZSM-11 molecular sieve raw powder; the NaZSM-11 molecular sieve raw powder was calcined at 560℃ for 10 hours, and then subjected to ammonium exchange in ammonium nitrate aqueous solution for 5 hours; the obtained material was sequentially separated, washed, and dried to obtain H-ZSM-11 molecular sieve raw powder; the H-ZSM-11 molecular sieve raw powder was calcined at 560℃ for 6 hours to obtain acidic H-ZSM-11 molecular sieve with a silicon-to-aluminum atomic ratio of 50.
[0075] Application Example 1 The catalysts prepared in Examples 1-5 and Comparative Examples 1-5 were reduced and pretreated at 400°C for 2 hours under a hydrogen atmosphere to obtain reduced catalysts. These reduced catalysts were then applied to the CO2 hydrogenation reaction to produce liquefied petroleum gas. The reaction conditions were: reaction temperature 350°C, reaction pressure 3 MPa, H2 to CO2 volume ratio 3:1, and H2 / CO2 gas space velocity 4000 mL / (h·g). The catalytic reaction results are shown in Tables 1 and 2.
[0076] Table 1. Catalytic performance of the catalysts prepared in Examples 1-5 and Comparative Examples 1-5 for CO2 hydrogenation to liquefied petroleum gas.
[0077] In Table 1, C1 represents the selectivity of methane, and C2... = -C4 = Indicates the selectivity of low-carbon olefins (ethylene, propylene, and butene), C3 0 -C4 0 Indicates the selectivity of low-carbon alkanes (propane and butane); C5 + This indicates the total selectivity of gasoline and liquid fuel fractions (or higher hydrocarbons); oxygenated compounds indicate the selectivity of methanol and dimethyl ether; Other HC indicates the selectivity excluding C1 and C2. = -C4 = C30 -C4 0 C5 + Selectivity for hydrocarbons other than oxygen-containing compounds.
[0078] Table 2. Yields of liquefied petroleum gas (LPG) in the CO2 hydrogenation process of catalysts prepared in Examples 1-5 and Comparative Examples 1-5.
[0079] As shown in Tables 1 and 2, the iron-zinc-zirconium composite oxide-molecular sieve catalyst provided by this invention exhibits excellent catalytic performance for CO2 hydrogenation to liquefied petroleum gas (LPG). The CO2 conversion rate reaches 23.02%, the LPG selectivity in total hydrocarbons reaches 80.06%, the methane selectivity in total hydrocarbons is less than 8.49%, and the CO selectivity does not exceed 44.97%. More importantly, the LPG yield reaches 10.22%. Comparative Example 1, using a zinc-zirconium composite oxide-molecular sieve catalyst, shows that the CO2 conversion rate and LPG yield are reduced to 15.25% and 6.89%, respectively. Comparative Example 2, using a physical mixing method to prepare the iron-zinc-zirconium composite oxide, achieves a methane selectivity of 13.74%, while the LPG selectivity and yield are reduced to 62.03% and 6.84%, respectively. Comparative Examples 3-5, using other acidic molecular sieves such as H-SAPO-34, HZSM-5, and H-ZSM-11, showed liquefied petroleum gas selectivity and yield of only 12.63-59.10% and 2.05-6.15%, respectively.
[0080] Application Example 2 The catalyst prepared in Example 1 was reduced and pretreated at 400°C for 2 hours under a hydrogen atmosphere to obtain a reduced catalyst. This reduced catalyst was then applied to the CO2 hydrogenation reaction to produce liquefied petroleum gas. The reaction conditions were: reaction temperature 375°C, reaction pressure 4 MPa, H2 to CO2 volume ratio 6:1, and H2 / CO2 gas space velocity 1000 mL / (h·g). The results are as follows: Figure 3 As shown.
[0081] Figure 3 The graph shows the catalytic performance of the iron-zinc-zirconium composite oxide-molecular sieve catalyst prepared in Example 1 in the reaction of carbon dioxide hydrogenation to liquefied petroleum gas. According to... Figure 3 It can be seen that after 500 hours of hydrogenation, the selectivity and yield of liquefied petroleum gas in the total hydrocarbons remained at 78.28% and 32.94%, respectively, and the CO2 conversion rate was 62.41%. However, the selectivity of methane in the total hydrocarbons was less than 8.89%, and the CO selectivity did not exceed 32.59%. This confirms that the iron-zinc-zirconium composite oxide and the acidic H-RHO molecular sieve catalyst have stable performance in the carbon dioxide hydrogenation to liquefied petroleum gas reaction.
[0082] As can be seen from the above examples and comparative examples, the iron-zinc-zirconium composite oxide-molecular sieve catalyst provided by the present invention can significantly improve the selectivity of liquefied petroleum gas in total hydrocarbons when used to catalyze the reaction of CO2 hydrogenation to liquefied petroleum gas, and can also effectively reduce the formation of methane and CO byproducts.
[0083] This document uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. Furthermore, those skilled in the art will recognize that, based on the ideas of the present invention, there will be changes in the specific implementation methods and application scope. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. An iron-zinc-zirconia composite oxide-molecular sieve catalyst, comprising an iron-zinc-zirconia composite oxide and an acidic H-RHO molecular sieve; wherein the iron-zinc-zirconia composite oxide contains 0.1-4% iron by mass and the molar ratio of zinc to zirconium is 0.1-1:
1.
2. The iron-zinc-zirconium composite oxide-molecular sieve catalyst according to claim 1, characterized in that, The mass ratio of the iron-zinc-zirconium composite oxide to the acidic H-RHO molecular sieve is 0.2~4:
1.
3. The iron-zinc-zirconium composite oxide-molecular sieve catalyst according to claim 1 or 2, characterized in that, The acidic H-RHO molecular sieve has a silicon-to-aluminum atomic ratio of 0.01 to 0.4:1; the size of the acidic H-RHO molecular sieve is 1 to 3 μm; and the particle size of the iron-zinc-zirconium composite oxide is 5 to 10 nm.
4. A method for preparing the iron-zinc-zirconium composite oxide-molecular sieve catalyst according to any one of claims 1 to 3, comprising the following steps: A composite metal ion salt solution is obtained by mixing water-soluble iron salt, water-soluble zinc salt, water-soluble zirconium salt, and water. The composite metal ion salt solution and an organic complexing agent are mixed to carry out a complexation reaction, thereby obtaining a colloidal solid precursor. The colloidal solid precursor was calcined to obtain an iron-zinc-zirconium composite oxide. The iron-zinc-zirconium composite oxide is mixed with acidic H-RHO molecular sieve to obtain the iron-zinc-zirconium composite oxide-molecular sieve catalyst.
5. The preparation method according to claim 4, characterized in that, The molar ratio of total metal ions to organic complexing agent in the composite metal ion salt solution is 1:0.25~5.
6. The preparation method according to claim 4 or 5, characterized in that, The organic complexing agent includes one or more of glucose, citric acid, salicylic acid and tartaric acid; the complexing reaction is carried out at a temperature of 50~90℃ for 2~10h.
7. The preparation method according to claim 4, characterized in that, The calcination treatment temperature is 300~800℃, and the holding time is 2~10h; the iron-zinc-zirconium composite oxide and the acidic H-RHO molecular sieve are mixed by mechanical grinding.
8. The application of the iron-zinc-zirconium composite oxide-molecular sieve catalyst according to any one of claims 1 to 3 or the iron-zinc-zirconium composite oxide-molecular sieve catalyst prepared by the preparation method according to any one of claims 4 to 7 in the catalytic hydrogenation of carbon dioxide to liquefied petroleum gas.
9. A method for producing liquefied petroleum gas by catalytic hydrogenation of carbon dioxide using an iron-zinc-zirconium composite oxide-molecular sieve catalyst, comprising the following steps: The iron-zinc-zirconium composite oxide-molecular sieve catalyst was subjected to reduction pretreatment to obtain a reduction catalyst; The mixture of H2 and CO2 is subjected to a hydrogenation reaction under the catalysis of the reduction catalyst to obtain liquefied petroleum gas; The iron-zinc-zirconia composite oxide-molecular sieve catalyst is the iron-zinc-zirconia composite oxide-molecular sieve catalyst according to any one of claims 1 to 3 or the iron-zinc-zirconia composite oxide-molecular sieve catalyst prepared by the preparation method according to any one of claims 4 to 7.
10. The method according to claim 9, characterized in that, The reduction pretreatment is carried out in a hydrogen atmosphere at a temperature of 300-500°C for 1-6 hours. The volume ratio of H2 to CO2 is 1~8:1; The space velocity of the H2 and CO2 mixture is 800~10000 mL / (h·g); The hydrogenation reaction is carried out at a temperature of 300~420℃, for a time of 10~1000h, and at a pressure of 0.5~6MPa.